TB financing in East Europe promotes unnecessary hospital admissions: the case of Armenia - Laura Gillini; Karapet Davtyan; Hayk Davtyan; Armen Hayrapetyan; Sergey Khachatryan; Rosella Centis; Lia D’Ambrosio; Masoud Dara; Giovanni Battista Migliori; Giovanni Sotgiu (Journal of Infection in Developing Countries)
This item has no abstract. Follow the link below to access the full text.